Adaptasi Bahasa dan Budaya Arab dalam Masyarakat Muslim Indonesia: Kajian Antropolinguistik Kualitatif: Penelitian - Meilisa, Amarqaila; Azizah, Siti Zahra; Ms, Aulia Habila; Suri, Nursukma (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the adaptation of Arabic language and culture in the lives of Indonesian Muslims through a qualitative anthropolinguistic approach. Arabic functions not only as a means of religious communication but also as a representation of cultural values, morals, and social identity. Data were obtained through observation, in-depth interviews with two informants (Mr. Arjali, 48, and Mrs. Arinovita, 47), and documentation of socio-religious activities. The results show that Arabic terms such as assalamu'alaikum (peace be upon you), alhamdulillah (praise be to God), and insyaallah (God willing) have become integrated into everyday conversation as expressions of politeness, religiosity, and togetherness. Meanwhile, the adaptation of Arabic culture is evident in clothing, greetings, and religious traditions that are adapted to the local context, creating a hybrid form of Indonesian Islamic culture. This study confirms that the synergy between Arabic language and culture forms a distinctive pattern of religious communication that strengthens the polite, moderate, and contextual Islamic identity of Indonesian society.